Getting started with Apple Watch development : Swift programming for watchOS - Sardal, Ravin (Apress, 2019)
"Create your own Apple Watch applications by learning the basics of Xcode and Swift, the programming language used for Apple application development. In this video, step-by-step instructions teach you how to independently navigate and utilize Apple's development toolkit and Xcode program. By the end you will be able to write functional code in Swift and engineer your own basic Apple Watch applications."--Resource description page